Pengelolaan Kekayaan pada High Net Wort Individual (HNWI)Studi pada Keluarga Huang - , Marianawati ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This research is case study with 1 client. Huang family (alias) is the client of this research. Huang family is a young family with 3 children, 8, 6, and 4 years old. The first problem that raise on this research is growth and accumulation assets for prepare children education and pension. Evaluation and analyse data will be based on financial data and risk tolerance client and his wife. From the risk tolerance measuring is knew that client is very conservative and his wife is moderat. The measuring will be the foundation to make portofolio rebalancing. In the process of rebalancing is porposed 3 scenario that based on the risk tolerance. From the 3 scenario clien and his wife will choose the best scenario. Client and his ife choose scenario 2 what are the highest return and moderat risk. Scenario 2 is the scenario that based on wifeâs risk tolerace. The scenario will implement on September 2011 and will complete on January 2012.